Manifesto Per La Satira e Per I Comici - Cassano, Giuseppe (Revista Amagis Jurídica, 2026)
The right of satire has a constitutional relevance and a complex foundation, consisting of being a creation of the spirit, of its relational dimension and its control function, carried out with irony and sarcasm towards the powers of any nature. Expressed in writing or through an oral or figurative form, satire constitutes a corrosive and often merciless criticism, based on a representation that emphasizes and deforms reality to provoke laughter. Although incompatible with the parameter of truth applied in libel and defamation cases, satire can never turn itself into a mere derision, contempt or destruction of the dignity of the person. The recent monologue by the comic duo Pio and Amedeo, on the “politically correctness” subject matter, reopens issues that have never been dormant